1994
DOI: 10.1111/j.1365-2958.1994.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

The HAP2,3,4 transcriptional activator is required for derepression of the yeast citrate synthase gene, CIT1

Abstract: The yeast nuclear gene CIT1 encodes mitochondrial citrate synthase, which catalyses the first and rate-limiting step of the tricarboxylic acid (TCA) cycle. Transcription of CIT1 is subject to glucose repression. Mutations in HAP2, HAP3 or HAP4 block derepression of a CIT1-lacZ gene fusion. The HAP2,3,4 transcriptional activator also activates nuclear genes encoding components of the mitochondrial electron transport chain, and thus it co-ordinates derepression of two major mitochondrial functions. Two DNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 50 publications
(31 reference statements)
4
25
0
Order By: Relevance
“…This was also reported previously Rosenkrantz et al, 1994a). Rosenkrantz et al (1994b) identified a functional Hap2/3/4 element at 291/ 273 in the CIT1 promoter, which might mediate the induction. An ORF with 54% similarity to CIT1 and 52% similarity to CIT2 was located at chromosome XVI, which was tentatively named CIT3 (Table 1).…”
Section: Glyoxylate Cyclesupporting
confidence: 88%
“…This was also reported previously Rosenkrantz et al, 1994a). Rosenkrantz et al (1994b) identified a functional Hap2/3/4 element at 291/ 273 in the CIT1 promoter, which might mediate the induction. An ORF with 54% similarity to CIT1 and 52% similarity to CIT2 was located at chromosome XVI, which was tentatively named CIT3 (Table 1).…”
Section: Glyoxylate Cyclesupporting
confidence: 88%
“…2). This induction suggests that Tor proteins may be upstream of the Hap2,3,4,5p complex known to regulate the transcription of citric acid cycle genes (21)(22)(23). However, rapamycin induced citric acid cycle gene expression slightly less strongly and more transiently than the diauxic shift, indicating that other complexities exist.…”
Section: Resultsmentioning
confidence: 96%
“…Such a regulation allows adaptation of the ␣-ketoglutarate supply both to the tricarboxylic acid cycle carbon flux and to glutamate synthesis. Regulation by glucose is sustained at least partly by the HAP complex, which activates the expression of the CIT1 and ACO1 genes (24,53), while the mechanism of repression in the presence of glutamate is not yet understood. a ␤-Gal assays were carried out with the GDH1-lacZ fusion integrated at the GDH1 locus of the wild-type strain BWG1-7a.…”
Section: Discussionmentioning
confidence: 99%